Determinants of Female Traders' Income in Sanglah Traditional Market Denpasar City - Rahmadi, Atillia Rizka; Dewi, Made Heny Urmila (CV. Lenggogeni Data Publishing, 2025)
This study aims to analyze the factors that influence the income of female traders in the Sanglah Traditional Market, Denpasar City. The independent variables include number of family dependents, distance from home to the market, working hours, and the presence of modern markets. This research uses a quantitative approach with an associative research design. Data were collected through questionnaires distributed to 93 respondents using a proportional stratified random sampling technique. The data were analyzed using multiple linear regression. The results show that simultaneously all independent variables significantly affect female traders' income. Partially, the number of family dependents and working hours have a positive and significant effect on income, while distance and the presence of modern markets have a negative and significant effect. The most dominant factor influencing income is working hours. This study provides implications for the government and market managers to pay more attention to the challenges faced by female traders, especially in competing with modern markets and managing productive working hours.